Prevalence of Coronary Artery Disease Socio Demographic Determinants in Low Socioeconomic Status Population - Riaz Ahmed Mangi, Atta Muhammad Chandio, Jawaid Hussain Lighari , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
To determine the prevalenceof coronary artery disease in low socioeconomic population. * To determine socio-demographic determinants of coronary artery disease in low socioeconomic population Methods: This crosssectional study was conducted in the department of cardiology Peoples Medical College Hospital (PMCH) Nawabshah, from April 2016 to September 2016.A total 1200 patient of coronary artery disease were enrolled. After information was gathered, from 298 cases with low socioeconomic status were questioned about age, gender, education. Result: Study result shows that the prevalence of coronary artery disease in low socioeconomic status population is 24.8%.The main variable found in the study is age and higher prevalence 52% found in the age group of 46-65 years group. This study result reveals that males (58%) and (42%) female, illiterate (68%) and53 % were those whose earning was between 10000-20000 showed prevalent groups. Conclusion: The study has highlighted high prevalence of coronary artery disease in low socioeconomic status population at Shaheed Benazir Abad. There is need to improve awareness regarding coronary artery disease and its socio demographic determinants with emphasis on life style modification and socioeconomic stability with development.